DESIGN AND CONTROL OF AIR CONDITIONING SYSTEM OPERATION MODES IN SURGICAL ROOM - KEZIA SIMANJUNTAK (NIM : 13311032); SETU KURNIANTO PUTRA (NIM : 13311060); , ESTHER
The surgical room's air conditioning system has been designed with multiple modes system's operation, namely sanitary mode, preparation mode, and operation mode. The room temperature and relative humidity design conditions at each mode respectively, 28 °C and 60 %, 24 °C and 55 %, and 21 °C and 55 %. Moreover, air pressure within surgical room is designed 15 Pa above ambient air pressure. Air temperature is controlled using electric heater with power capacity 12 kW. Relative humidity of air inside the surgical room is controlled using direct expansion air conditioner with cooling capacity 54 kW. Direct expansion air conditioner uses two compressors, with cooling capacity 28 kW each. Indoor air pressure is controlled by combining exhaust air damper's opening, which has three opening position, 0 %, 27,5 %, and 100 %, and exhaust fan's speed, which has two speed mode, slow and fast. Control of the thermal conditions involves several components, direct expansion air conditioner unit, electric heater, damper, and fan. These components are controlled using relay system based on operating conditions in each mode. Electric heater is controlled based on the alteration of supply air temperature. The number of active compressors, dampers' openings, and exhaust fan's speed depend on operation mode of air conditioning system, while the activation of compressors themselves are controlled by the air temperature after cooling coil and refrigerant pressure after evaporator. In addition, there is also interlock logic between doors, which are located in the surgical room to control indoor air pressure. The mathematical model based simulation results using software Matlab showed that, the required time to achieve steady room temperature, humidity ratio, and relative humidity respectively 250 seconds, 260 seconds, and 650 seconds. While the time required for air pressure room to become equal with the pressure outside room, is 28 seconds.